A Complete Prefeasibility Evaluation of On-Site Energy Generation System (2022)
The recent global concern to mitigate the ecological impact on energy production has promoted the search for alternatives that allow a better use of resources. In this panorama, the cogeneration process appears as a solution seen with good eyes thanks to its great efficiency, which is why many institutions and companies have opted for the transition from the traditional system of energy production to cogeneration. This article develops the selection of the best alternative among different suppliers to implement a cogeneration system in an energy production plant, taking into account economic factors, selecting the one that represents the greatest profitability in the shortest time.